2007
DOI: 10.1590/s0100-40422007000200024
|View full text |Cite
|
Sign up to set email alerts
|

Emissão de mercúrio para a atmosfera pela queima de gás natural no Brasil

Abstract: Recebido em 23/2/06; aceito em 16/5/06; publicado na web em 26/9/06 MERCURY EMISSIONS TO THE ATMOSPHERE FROM NATURAL GAS BURNING IN BRAZIL. Increasing natural gas use in Brazil triggered a discussion of its role as a Hg source. We show that Hg emissions to the atmosphere from fossil fuel combustion for power generation in Brazil contribute with 6.2% (4.2 t yr -1 ) to the total anthropogenic Hg atmospheric emissions, with coal combustion and biomass burning as major sources. Natural gas contributes with 0.04 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
1
0
4
Order By: Relevance
“…A forma particulada é a forma dominante de Hg no processo de lixiviação dos solos, sendo esta influenciada pela deposição oriunda de atividades antrópicas (Lacerda e Gonçalves 2001;Lacerda et al 2007). Já o Hg dissolvido, não diferentemente de outros elementos metálicos, é fortemente adsorvido nos sedimentos e MPS, incluindo a matéria orgânica, e principalmente nos óxidos e hidróxidos de Fe e Mn.…”
Section: Transporte E Sedimentação Metálicaunclassified
See 1 more Smart Citation
“…A forma particulada é a forma dominante de Hg no processo de lixiviação dos solos, sendo esta influenciada pela deposição oriunda de atividades antrópicas (Lacerda e Gonçalves 2001;Lacerda et al 2007). Já o Hg dissolvido, não diferentemente de outros elementos metálicos, é fortemente adsorvido nos sedimentos e MPS, incluindo a matéria orgânica, e principalmente nos óxidos e hidróxidos de Fe e Mn.…”
Section: Transporte E Sedimentação Metálicaunclassified
“…O Hg é um elemento que está presente em condições naturais na crosta terrestre, água, biota e atmosfera. (Lacerda et al 2007). As fontes naturais são decorrentes de eventos tectônicos que promoveram a formação da bacia sedimentar em associação a derrames basálticos sobre o oceano, isso aproximadamente entre 2,5 Ba no chamado ciclo Transamazônico, no Éon Proterozóico, e 450 Ma na Era Mesozóica (Dall'Agnol e Rosa -Costa 2008).…”
Section: Introductionunclassified
“…Mais detalhes sobre o uso de fatores de emissão para estuários da região NE, suas limitações e aplicações podem ser encontrados na literatura especializada. 21,22,41,42 …”
Section: Estimativas De Cargasunclassified
“…24,25 It is known that Hg has a high affinity for Au, through the formation of an amalgam, mainly in mining processes. 26 Recently, some studies have shown that different species of mercury (Hg 0 , Hg 2+ and CH 3 Hg + ) are easily adsorbed and desorbed in the structure of Au when high temperatures are applied, thus making easier the determination of Hg. 27,28 Some applications of pre-concentration of Hg in Au columns (gold traps) followed by determination using atomic spectrometry techniques have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%